660 Trapeziectomy Versus Joint Replacement for First Carpometacarpal (CMC-1) Joint Osteoarthritis: A Systematic Review and Meta-Analysis. (12th October 2021) - Raj, S; Clay, R; Ramji, S; Shaunak, R; Dadrewalla, A; Sinha, V; Shaunak, S
Abstract: Aim: The challenge of managing first carpometacarpal (CMC-1) joint osteoarthritis is the lack of guidance on which surgical intervention is superior. This systematic review and meta-analysis compares joint replacement (JR) and trapeziectomy techniques to provide an update. Method: In August 2020, MEDLINE, Embase and Web of Science were searched for eligible studies that compared these two techniques for the treatment of CMC-1 joint osteoarthritis (PROSPERO registration ID: CRD42020189728). Primary outcomes included the Disabilities of the Arm, Shoulder and Hand (DASH), QuickDASH and pain visual analogue scale (VAS) scores. Secondary outcomes, such as total complication, dislocation, and revision surgery rates, were also measured. Results: From 1909 studies identified, 14 studies (1005 patients) were eligible. Our meta-analysis found that post-operative QuickDASH score was lower for patients in the JR group, indicating decreased disability following this technique (5 studies, p = 0.0002). However, pain VAS scores were similar between the two groups (5 studies, p = 0.22). Interestingly, JR techniques had significantly greater odds of overall complications (12 studies; OR 2.27; 95% CI 1.17-4.40, p = 0.02) and significantly greater odds of revision surgery (9 studies; OR 5.14; 95% CI 2.06-12.81, p = 0.0004). Conclusions: Overall, based on low to moderate quality evidence, we found that JR treatments may result in better function with less disability with comparable pain (VAS) scores; however, JR has greater odds of complications and greater odds of requiring revision surgery. More robust RCTs that compare JR and TRAP with standardised outcome measures and long-term follow-up would add to the overall quality of evidence.